An exploratory study of the academic engagement and beliefs of Latino male high school students. Issue 4 (4th July 2017) - Torres, Mellie
Abstract: This study provides insights to the school experiences of Latino male students through an exploration of how they describe their beliefs about education and how they engage in school for academic success. Data is drawn from interviews and surveys conducted with Latino males that participated in New York University's Black and Latino Male School Intervention Study (BLMSIS) between 2006 and 2011. The findings revealed a dynamic interplay among how the students 'do school' (behavioral engagement), their intellectual involvement (cognitive engagement), and their strong beliefs in the education for social mobility shaped schooling for them. This focus on the experiences of young Latino males seeks to assist researchers, policymakers, and practitioners alike design and implement programs and policies to promote their educational progress and success.